The Implementation of Community Based on Total Sanitation among Fisherman Families in West Java (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
The aim of this study was to obtain a picture on the implementation of Sanitasi Total Berbasis Masyarakat (STBM) the Indonesian term for Community Led Total Sanitation (CLTS) among the families of fisherman in Eretan Kulon, Indramayu West Java. Participants of this Household Survey were categorized into two, namely households that have under-five children and households that have youth. Father or mother or any adult who live with under-five children or youth were purposively chosen as the participants of this study. In total 307 Households (HH Under five 51.14%; HH Youth 48.86%) participated in this study. Five pillars of STBM were used to develop a questionnaire for this HH Survey. The result revealed that among the five pillars of STBM, the highest mean score was in safe management of drinking water and food (Mean=4.08), followed by washing hands with soap (Mean=3.45), management of solid waste (Mean=2.79), management of liquid water (Mean=2.64), and open defecation (Mean=1.90). The result of this study indicated that not all families have latrines so that they still practice of open defecation. The study also showed that solid and liquid waste management is still not considered important to maintain health and environmental hygiene.